Phil Skiba on exercise and health during COVID-19 crisis - Skiba, P. (Supporting champions, 2020)
In today`s special episode I talk to Dr Phil Skiba, Director of Sports Medicine for the Advocate Aurora Medical Group in Chicago, one of the largest in the United States and one of sharpest people I know - a true polymath, about the current crisis, his observations, his advice about us for general health, staying physically fit and training and more broadly our responsibilities to ourselves, each other and why and how this situation arose and what this all might mean.